The mechanism of protection of human rights (Journal of actual problems of jurisprudence, 2019)
The mechanism of protection of civil rights acts in a political, social, socio-psychological context, which may reduce theeffectiveness of human rights institutions or, conversely, increase their effect. most sophisticated legal mechanisms and procedureswill be powerless in the unstable political situation, the collapsing economy, the loss of values, moral degradation, social and nationalconfrontation. These adverse conditions have developed in the present society. Therefore, the work associated with the improvement ofthe legal means of protecting human rights and freedoms is inseparable from the system of measures to normalize the situation in thecountry. For such measures must be based on analysis of the reasons for this unfortunate situation and to identify ways to overcome it.